Pengaruh Kesesuaian Kerja terhadap Keterampilan Kerja dengan Keterikatan Kerja sebagai Variabel Mediasi - Firda Ayu Noviyana (Universitas Negeri Surabaya, 2018)
This study aims to identify and explain the influence of person job fit, job crafting and work engagement in Semen Indonesia Company. This study used saturated sample with the sample 50 respondents. Methods of the statistical analysis that used were SEM Partial Least Square (PLS) with smartPLS 2.0 sofware. The results of this research explained that person job fit has a positive to job crafting. Work engagement posiive to job crafting. Person job fit positive to work engagement. And work engagement not mediates the person job fit and job crafting.